2005
DOI: 10.1007/s00402-004-0791-1
|View full text |Cite
|
Sign up to set email alerts
|

High secondary displacement rate in the conservative treatment of impacted femoral neck fractures in 105 patients

Abstract: In our group of patients, secondary displacement was frequent and unpredictable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 18 publications
1
21
1
1
Order By: Relevance
“…In our study, fractures classified as Garden II had a 3-times higher risk of experiencing SED, which may explain the higher rate of SED compared to previously published studies [5,9,10]. Our hospital internal guidelines recommended non-operative treatment only for Garden I fractures; however, 37 % of non-operatively treated patients likely had in fact a Garden II fracture which highlights the problem of inter-observer variation and accuracy of the diagnostic process.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…In our study, fractures classified as Garden II had a 3-times higher risk of experiencing SED, which may explain the higher rate of SED compared to previously published studies [5,9,10]. Our hospital internal guidelines recommended non-operative treatment only for Garden I fractures; however, 37 % of non-operatively treated patients likely had in fact a Garden II fracture which highlights the problem of inter-observer variation and accuracy of the diagnostic process.…”
Section: Discussioncontrasting
confidence: 68%
“…Non-operative treatment avoids risks of an operation and postoperative complications, particularly in elderly patients; this treatment, however, was reported to fail in many patients leading to secondary displacement (SED) with rates reported between 14 and 52 % [5,[9][10][11], as observed in our clinic. SED is manifested by pain exacerbation associated with the loss of impaction of the fracture or displacement of a primary undisplaced fracture.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…This statement is based most notably on two large studies, from Otremski, et al [3] and Raaymakers and Marti [11], which showed no correlation between fracture angle and secondary displacement and/or nonunion in impacted femoral neck fractures. Verheyen et al [12] determined that the critical angle between Grade I and Grade II injuries is impractical, since almost all cases of impacted femoral neck fractures lie in the gray area and it is too difficult to differentiate them. However, in his original 1935 work, Pauwels [1] emphasized the exceptional nature of impacted femoral neck fractures (Figure 1).…”
Section: Copyright © 2010 Scires Jbisementioning
confidence: 99%